Corrosion performance of friction surfaced nickel aluminium bronze (NAB) alloy under erosion corrosion and salt fog environment. (13th March 2018) - Rajakumar, S.; Balasubramanian, V.
ABSTRACT: In the present research work, the extruded nickel aluminium bronze (NAB) alloy is friction surfaced over cast NAB alloy as a repairing technique for the deteriorated marine components. The friction surfaced specimens were tested for their corrosion properties. The corrosion tests such as salt fog test, erosion–corrosion test and pitting corrosion test were conducted to investigate the corrosion behaviour of the friction surfaced NAB alloy. It is found that the accumulation of corrosion occurred due to the presence of a continuous network of the ΚIII-phase. The lower corrosion rate is achieved in friction surfaced NAB alloy compared to the base NAB alloy which is contributed by the corrosion resistant contents such as Al and Cu and also by the fine grain microstructure obtained during the friction surfacing process. This paper is part of a supplementary issue from the 17th Asia-Pacific Corrosion Control Conference (APCCC-17) .